Awareness on 3R practice: a case study at UTHM Pagoh residential college - Ali, Roslinda; Lim, Chun Lan; A. Hamid, Hazren; Muhamad, Mimi Suliza; Hamidon, Nuramidah; Harun, Hasnida; Mohamed Sunar, Norshuhaila (Penerbit UTHM, 2020)
Solid waste can be defined as any scrap material; or unwanted surplus substance; or rejected products arising from the application of any process [1]. This also includes any substance required to be disposed of as being broken, worn out, contaminated or otherwise spoiled. Over the years, the problems of solid waste generation are increasing all over the world. In the year 2016, cities around the world generated 2.01 billion tonnes of solid waste, amounting to a footprint of 0.74 kilograms per person per day [2]. With rapid population growth and urbanisation, the annual waste generation is expected to increase to 3.4 billion tonnes by year 2050. The same trend can be seen in Malaysia. The waste generation rate in this country has been steadily increasing from 12.3 million tonnes in year 2013 to 13.9 million tonnes in year 2018 [3]. This amount is expected to increase to 14.4 million tonnes by year 2020.